Utilization of end-of-life tire fibers in Portland cement-based composites applied in buildings - Paya, Jordi (2016)
Tires out of use (NFU) and its management is a problem in many countries of the world, and even developing countries like Perú , for lack of separate collection and proper management system. Fluid catalytic cracking catalyst (FCC) a waste product of the oil industry and can be obtained from refineries PetroPerú . Portland cement mortars were experienced with tire incorporating fibers (FN) as a substitute for aggregate (siliceous limestone) in a proportion of 25% by volume and 100% mortars FN. The results show a loss of workability and trials show that this material can be used in construction applications improving their thermal properties and reaching compressive strength values ranging from 25.68 to 9.30 MPa. Acceptable values to produce masonry units. The use of tire fibers (FN) in Portland cement mortars (CP) and CP-FCC feedstock can be a good ecological alternative and obtain unconventional precast low economic and environmental cost.